The medium‐run effects of a foreign election intervention: Haiti's presidential elections, 2010–2015. (Contemporary Economic Policy, 2022)
The US and other foreign actors often intervene in elections in countries transitioning to democracy. I examine the effects of such interventions on voter behavior. In 2010, the United States intervened in Haiti's presidential election, advancing Michel Martelly over Jude Célestin. I look at the relationship between the intervention and voter behavior in the next election using Célestin's 2010 vote share as a measure of the intervention's intensity in a modified difference‐in‐differences analysis. Areas with greater Célestin support in 2010 had lower turnout in 2015. The relationship is robust to many sensitivity tests that account for possible confounding effects from fraud.